2014
DOI: 10.1186/bf03351565
|View full text |Cite
|
Sign up to set email alerts
|

Solar flare effects on the geomagnetic elements during normal and counter electrojet periods

Abstract: The paper describes the study of solar flare effects (sfe) on horizontal (H ), eastward (Y ) and vertical (Z ) components of the geomagnetic field at the Indo-USSR chain of magnetic observatories extending from the magnetic latitudes 0• to 45• N, a network not available any where else in the world. Events are selected when strong, normal and reversed (counter) equatorial electrojet are in existence as well as when only a partial counter electrojet is present.During a strong and normal electrojet event time, sf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 25 publications
6
66
1
2
Order By: Relevance
“…These studies have shown that SFE (H) amplitude is lower at equator and higher for stations outside the jet due to the counter electrojet related decreasing effect on H . The characteristics of the electrojet response, to solar flares, under conditions of counter electrojet, have been described by Rastogi et al (1999). They have also confirmed the existence of zonal and meridional components of the ionospheric currents over the equatorial latitudes, which in combination with S q currents produce complex effects (as seen during flares occurring at the time of partial CEJ events).…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…These studies have shown that SFE (H) amplitude is lower at equator and higher for stations outside the jet due to the counter electrojet related decreasing effect on H . The characteristics of the electrojet response, to solar flares, under conditions of counter electrojet, have been described by Rastogi et al (1999). They have also confirmed the existence of zonal and meridional components of the ionospheric currents over the equatorial latitudes, which in combination with S q currents produce complex effects (as seen during flares occurring at the time of partial CEJ events).…”
Section: Introductionmentioning
confidence: 53%
“…They have explained the observed irregular variations of Z components at different stations in terms of possible distortions in the altitude profile of the ionospheric currents at low latitudes. Several studies have reported the effects of solar flares during counter electrojet events (Srivastava, 1974;Sastri, 1975;Rastogi et al, 1975Rastogi et al, , 1999Rangarajan and Rastogi, 1981;Manju and Viswanathan, 2005). These studies have shown that SFE (H) amplitude is lower at equator and higher for stations outside the jet due to the counter electrojet related decreasing effect on H .…”
Section: Introductionmentioning
confidence: 99%
“…In response to flare enhancement in the X-ray flux, the H component shows a strong and rapid increase at all the stations. This sudden intensification in the H component is a signature of the response of the global ionospheric S q and the EEJ current systems to the sudden conductivity enhancement, caused by the flare X-ray ionization (Richmond and Venkateswaran, 1971;Rastogi et al, 1999). The red arrows mark the time of the peaks in H intensification at each of the stations.…”
Section: Model Simulations By Supim-inpementioning
confidence: 99%
“…The EEJ response under solar flare events has been extensively investigated and documented in the literature. Besides the sudden increase in the ionization density by the flare radiation, the EEJ enhancement is also shaped by the background electric field (Abdu et al, 2017;Zhang et al, 2017;Rastogi et al, 1999). In the present work, we analyze the responses of the ionospheric current system during two solar flare events that occurred near midday on 13 May 2013 and 11 March 2015; both events occur during geomagnetic quiet days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation